Quantum computers: where physics meets computer science - MAVROGIORGOU, SOFIA (Open Schools Journal for Open Science, 2026)
Quantum Physics is defined as “the study of matter and energy at the most fundamental level”. It has entirely transformed our perspective of the physical world and is also the foundation of numerous technological advancements. More specifically, quantum mechanics has been applied in sectors such as medicine and biology, with quantum computing emerging as the most prominent among them. [5] The primary objective of this study is to analyse the concepts of quantum computing, focusing on what quantum computers are, how they function, as well as outline and explain the differences between them and standard computational models (classic computers). Furthermore, their relation to the laws of physics will be discussed. Secondarily, this article aims to provide recent achievements, such as existing quantum computers and plans concerning the future so as to underline the role quantum physics will play, shaping the frontier of computation.